Change in NT-proBNP (N-Terminal Pro-B-Type Natriuretic Peptide) Level and Risk of Dementia in Multi-Ethnic Study of Atherosclerosis (MESA). Issue 2 (February 2020) - Ostovaneh, Mohammad R.; Moazzami, Kasra; Yoneyama, Kihei; A. Venkatesh, Bharath; Heckbert, Susan R.; Wu, Colin O.; Shea, Steven; Post, Wendy S.; Fitzpatrick, Annette L.; Burke, Gregory L.; Bahrami, Hossein; Sanchez, Otto A.; et al.
Abstract : Cross-sectionally measured NT-proBNP (N-terminal pro-B-type natriuretic peptide) is related to incident dementia. However, data linking changes in NT-proBNP to risk of future dementia are lacking. We aimed to examine the association of change in NT-proBNP over 3.2 years with incident dementia. We included 4563 participants in MESA (Multi-Ethnic Study of Atherosclerosis) prospective cohort who were free of cardiovascular disease at enrollment, had NT-proBNP level measured at MESA exams 1 (baseline, 2000–2002) and 3 (2004–2005), and had no diagnosis of dementia before exam 3. The association of change in NT-proBNP level between MESA exams 1 through 3 and all-cause hospitalized dementia (by International Classification of Diseases, Ninth Revision, codes) after MESA exam 3 (2004–2005) through 2015 was assessed using competing-risks Cox proportional hazard regression analysis. During 45 522 person-years of follow-up, 223 dementia cases were documented. Increase in log-NT-proBNP from MESA exams 1 through 3 was positively associated with incidence of dementia (multivariable hazard ratio, 1.28 [95% CI, 1.001–1.64]; P =0.049). An increase of at least 25% in NT-proBNP level from MESA exam 1 through 3 was associated with a 55% ( P =0.02) increase in the risk of dementia in multivariable analysis. Addition of temporal NT-proBNP change to a model including risk factors and baseline NT-proBNP improved the prediction of dementia (Harrell C statistic from 0.85 to 0.87, P =0.049). Increase in NT-proBNP is independently associated with future all-cause hospitalized dementia and offers a moderately better predictive performance for risk of dementia compared with risk factors and baseline NT-proBNP. Clinical Trial Registration—: URL: https://www.clinicaltrials.gov . Unique identifier: NCT00005487. Abstract : Supplemental Digital Content is available in the text.